Climate cooperation as development policy: the case Of Costa Rica. (1st January 2000) - Dutschke, Michael; Michaelowa, Axel
Project-based climate cooperation between industrial and developing countries was first proposed in the early l990s, then under the name of joint implementation (JI). Once in place, this cooperation could lead to a high amount of additional financial flows to developing countries. Nevertheless, many NGOs and developing country representatives were in the beginning very sceptical about JI and feared it would not take into account development priorities and create new kinds of dependence on industrial countries. Therefore, developing countries and industrial countries found a compromise at the Berlin Conference of the Parties as they instituted a pilot phase for so-called activities implemented jointly (AIJ), lasting until 2000. Since the Kyoto conference, this concept has existed in the design of the Clean Development Mechanism (CDM), which allows for industrialised countries to account this kind of activity against their national obligation for greenhouse gas reduction, starting with the year 2000. This paper discusses the first results of the Au pilot phase in Costa Rica, which is important for the evaluation of the whole pilot phase and the ultimate design of the CDM. Costa Rica has a relatively high level of economic and social development and a well-developed environmental policy, which is comparable with that of advanced industrial countries. It is a major destination for ecotourism. Nevertheless, it suffers from high deforestation, owing to unequal distribution of land, migration and cattle ranching, as well as plantation expansion. Moreover, transport emissions are rising rapidly and fossil fuel electricity generation is growing, despite a target of phasing out fossil fuels completely. Building on a broad knowledge base, Costa Rica was able to develop creative environmental policy instruments, such as debt-for-nature swaps and biodiversity prospecting, to attract foreign funding. It is not surprising that it was the first developing country to open an JI office, develop project approval criteria and host AIJ pilot projects. The framework for climate cooperation in Costa Rica can therefore be described as ideal compared with the average developing country. After an initial phase of single bilateral projects, the Costa Rican JI office tried to attract more finance by offering certified tradeable carbon certificates resulting form these projects' offsets. Now it encourages multi-sector large-scale programmes, where transaction costs are lower and coherence with national development objectives can be more easily checked. It directs its attention to public Au investors, such as the Norwegian government. The renewable energy projects suffer from the unrealistic target to phase out fossil fuels by 2001, thus making AIJ projects in this sector impossible from that time. Therefore, the bulk of projects concern forestry, which is prone to uncertainties in the calculation of emission sequestration. A comparison of the estimates shows wildly differing assumptions in baselines and the sequestration capacity of the forests. Whether actual project implementation conforms to the plans remains to be seen. The analysis of the Costa Rican case shows that climate cooperation can be successful in the long run only if the industrial countries offer incentives for investors and if baseline determination rests on a clear set of guidelines. Human and technical capacities are necessary but not sufficient conditions for successful climate cooperation projects in developing countries. They seem to be able to prevent complete project failures, however, and can lead to innovative approaches. The issue will be settled only if large-scale investment is forthcoming under a regime of legally binding emission targets for industrial countries, as stipulated in the Kyoto Protocol. Then the ability to process a huge number of project proposals and to check whether they conform to development priorities, as well as monitoring and verification, becomes crucial.